Right Ventricular Assist Device Configuration for Remote Decannulation. Issue 3 (May 2016) - Tchantchaleishvili, Vakhtang; Sagebin, Fabio; Massey, Howard Todd
Preoperative risk factors, intraoperative fluid shifts, and transfusions place patients at increased risk for right ventricular failure during left ventricular assist device implantation. Despite aggressive use of inotropes and pulmonary vasodilators, in severe cases of RV failure, a right ventricular assist device may be required. For the past several years, we have been implanting right ventricular assist devices in the presented configuration, allowing less invasive removal without sternotomy. The method is presented herein.